2019
DOI: 10.1101/861781
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Parsing multiomics landscape of activated synovial fibroblasts highlights drug targets linked to genetic risk of rheumatoid arthritis

Abstract: One Sentence Summary: SFs under synergistic inflammation is associated with RA heritability, and MTF1 and RUNX1 could be crucial for the pathogenic chromatin rearrangement. Abstract:In rheumatoid arthritis (RA), synovial fibroblasts (SFs) produce a variety of pathogenic molecules in the inflamed synovium. Despite their potential importance, comprehensive genetic network of SFs under inflammatory conditions remains elusive. Here, to elucidate the actions of SFs and their contributions to RA pathogenesis, SFs, s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…In some reports, transcriptomic data proved useful for patient stratification. In RA, synovial fibroblasts (SFs) play important roles in joint inflammation [ 28 ] and show a dynamic response to inflammation at the epigenomic and transcriptomic levels [ 29 ]. Lewis et al .…”
Section: Introductionmentioning
confidence: 99%
“…In some reports, transcriptomic data proved useful for patient stratification. In RA, synovial fibroblasts (SFs) play important roles in joint inflammation [ 28 ] and show a dynamic response to inflammation at the epigenomic and transcriptomic levels [ 29 ]. Lewis et al .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they also expressed several proteinases such as ADAMTSs and MMPs [66]. Tsuchiya et al showed that the responses of OA-SFs to the stimulation of in ammatory cytokines were shared in RA-SFs, indicating the common potential for proin ammation in expanded cells derived from OA, RA [67], and probably healthy synovium. Furthermore, other groups demonstrated that hSSCs either from healthy subjects or OA patients could induce osteoclastogenesis from PBMCs in vitro [68].…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, a complex multidimensional study in RA fibroblast-like synoviocytes (FLS), an aggressive phenotype of fibroblasts in RA, was performed with the objective of establishing a high-resolution epigenomic landscape in RA. This study included histone modifications, open chromatin, RNA expression and DNA methylation analysis in RA FLS [ 68 ]. The effect of variants on histone regions is relevant, as seen in SLE.…”
Section: Epigenomics Studiesmentioning
confidence: 99%